Análisis semiótico de la danza: APU, cerros vivos. - Chiluisa Palacios, Jeimi Carolina (2015)
The cultural resistance of people against the reproach of power are areas of demonstrations, where using the symbolism express and communicate their beliefs, needs and desires. So, generate codes with their worldview. The Apu, live hills, dance is an artistic work that interrelates a number of ideas from symbolic processes present in ancestral and indigenous participation in community surveys. The work was created to represent indigenous issues in Ecuador and their struggle to be made visible in national society. In the analysis of the work it is to discover the profound reality expressed through the use of signs and other elements of speech. The meanings are under the guise of proxemics, quinésica, drama, music, etc. Therefore, this study was conducted in the light of the concepts of syntax, semantics and pragmatics that develop nonverbal cues, particularly the image. To zoom in and dive into the work was necessary to interview the author, and some of the actors. Similarly, the historical context in which the work was created was revised.